An approach to evaluate metabolite-related phototoxicity with combined use of photochemical properties and skin deposition. (10th October 2021) - Seto, Yoshiki; Tonami, Ryo; Iyama, Yosuke; Sato, Hideyuki; Onoue, Satomi
Highlights: A photosafety evaluation system of a chemical and its metabolites is required. Imipramine and its metabolite, desipramine, were employed as model compounds. Their photosafety was assessed based on the photochemical and skin exposure data. The outcomes showed great contribution of a metabolite to chemical phototoxicity. The comprehensive evaluations would provide reliable photosafety information. Abstract: Some chemicals have been reported to cause metabolite-related phototoxicity, and this study aimed to verify the applicability of photosafety assessment based on photochemical and pharmacokinetic properties to evaluate the metabolite-related phototoxicity risk. The phototoxic risk of imipramine (IMI) and its metabolite, desipramine (DMI), was evaluated by photochemical and pharmacokinetic analyses. IMI and DMI were found to have similar photoreactivities based on the generation of reactive oxygen species. The skin concentrations of IMI and DMI reached maximal levels at approximately 1 and 4 h, respectively, after oral administration of IMI (10 mg/kg), and DMI showed high skin deposition compared with IMI. According to the results, DMI was identified as a contributor to phototoxicity induced by orally-taken IMI. In in vivo phototoxicity testing, ultraviolet A irradiation from 3 to 6 h after oral administration of IMI (100 mg/kg) caused more potent phototoxic reactions compared with that from 0 to 3 h, and DMI yielded by metabolism of IMI would be associated with phototoxic reactions caused by orally-administered IMI. In addition to the data on IMI, a parent chemical, photochemical and pharmacokinetic profiling of its metabolite, DMI, led to reliable phototoxicity prediction of orally-administered IMI. Thus, characterization of the photosafety of metabolites would generate reliable information on the phototoxicity risk of parent chemicals, and the proposed strategy may facilitate comprehensive photosafety assessment of drug candidates in pharmaceutical development.